Long-term outcomes following percutaneous coronary intervention to an unprotected left main coronary artery in cardiogenic shock. (1st June 2020) - Yeoh, Julian; Andrianopoulos, Nick; Reid, Christopher M.; Yudi, Matias B.; Hamilton, Garry; Freeman, Melaine; Noaman, Samer; Oqueli, Ernesto; Picardo, Sandra; Brennan, Angela; Chan, William; Stub, Dion; et al.
Abstract: Background: In cardiogenic shock with severe left main coronary artery stenosis (LM), limited information exists on short and longer-term outcomes. We sought to determine the outcomes of unprotected LM PCI in cardiogenic shock. Methods: Excluding patients with previous CABG, consecutive patients undergoing PCI in cardiogenic shock from the Melbourne Intervention Group registry between 2005 and 2013 were analysed. Those post LM PCI were compared to those post non-LM PCI. Patient and procedural data were collected with 30-day and 12-month follow-up. Australian National Death Index linkage was performed for long-term mortality analysis. Results: After excluding previous CABG, 18, 069 procedures were performed during 1st January 2005 to 30th November 2013, 601 procedures in the setting of cardiogenic shock. Of these, 45 were performed to an isolated LM and 556 to a non-LM. Those with LM PCI were older and more likely to have a baseline left ventricular ejection fraction (LVEF) of <45%. The in-hospital, 30-day, 12-month and long-term mortality to 9 years in cardiogenic shock after LM PCI was 64.4%, 66.7%, 73.3% and 80.0% compared to 36.5%, 36.9%, 40.5% and 46.0%, after non-LM PCI (p < 0.001). On multivariate analysis, LM PCI was a significant independent predictor of long-term mortality (HR1.59, 95%CI 1.00–2.53, p = 0.048). Landmark analysis of survivors to discharge found the long-term mortality of LM PCI approaches 60% compared to 27% for those with non-LM PCI (p = 0.003). Conclusion: Long-term outcomes after PCI to LM in cardiogenic shock are poor, with much of the excess in mortality occurring early. However, reasonable long-term survival was found beyond the initial high-risk period. Highlights: In cardiogenic shock with severe left main coronary artery stenosis, limited amount of information is available on outcomes. Outcomes after PCI to the LM in cardiogenic shock are poor, with an excess of early mortality. Reasonable long-term survival was found beyond the initial high-risk period. LM PCI in cardiogenic shock was a significant independent predictor of long-term mortality. Research should focus on the utility of cardiogenic shock centres and mechanical support devices.